Jamaluddin Al-Afghani: "API" PAN-ISLAMISME DAN KEGIATAN POLITIK - Sirojuddin AR, D. (Buletin Al-Turas, 2004)
Jamaluddin AlAfghani was like a motivating spirit everywhere. He was a 19th century moslem reformist who propaganded theÂ unity of Islam through his Pan-IsLamism movement.Â